2009
DOI: 10.1183/09031936.00051309
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein and procalcitonin as predictors of survival and septic shock in ventilator-associated pneumonia

Abstract: We evaluated the performance of procalcitonin (PCT) and C-reactive protein (CRP) threshold values and kinetics as predictors of ventilator-associated pneumonia (VAP) survival and septic shock development.45 adult patients with VAP were studied. Serum CRP and PCT levels and the Sequential Organ Failure Assessment (SOFA) score were measured on days 1, 4 and 7 (D1, D4, D7) of VAP and their variations between different days (kinetics) were calculated (DPCT, DCRP). A multivariate logistic regression model was const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
2
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 38 publications
3
71
2
7
Order By: Relevance
“…AUC values were slightly better on day 3 and 5 after VAP onset (data not shown) However, since parameters assessed at VAP onset are statistically more robust and clinically more relevant we focused on the very first day. Nonetheless, our figures are lower than those described by others [20,21,50]. DUFLO et al [20] reported an AUC of 0.79 using PCT for predicting VAP-associated mortality.…”
Section: Combination Of Mr-proanp Pct and Icu Scorescontrasting
confidence: 55%
“…AUC values were slightly better on day 3 and 5 after VAP onset (data not shown) However, since parameters assessed at VAP onset are statistically more robust and clinically more relevant we focused on the very first day. Nonetheless, our figures are lower than those described by others [20,21,50]. DUFLO et al [20] reported an AUC of 0.79 using PCT for predicting VAP-associated mortality.…”
Section: Combination Of Mr-proanp Pct and Icu Scorescontrasting
confidence: 55%
“…It has been demonstrated that CRP may take part in the pathogenesis of atherosclerosis through the promotion of endothelial cell activation and foam cell generation within the arterial wall (19,20). Previous studies have identified the significant role of the serum CRP level in the development and prognosis of pneumonia, and have reported that an increased serum level of CRP may be present in patients with pneumonia (21,22). In particular, it has been found that the serum CRP level may be useful for distinguishing bacterial pneumonia from nonbacterial pneumonia in children, as higher serum CRP concentrations were observed in cases with a bacterial etiology (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…SIRS was defi ned as the presence of two or more of the following: temperature greater than 38 °C or less than 35 °C, heart rate greater than 90 bpm, respiratory rate greater than 20 bpm or PaCO 2 <32 mmHg, white blood cell count greater than 12×10 9 /L or less than 4.0×10 9 /L or relative count of immature cells greater than 10% of total leukocytes. [6] Shock was defined as systolic blood pressure <90 mmHg or 40 mmHg lower than basic blood pressure for more than one hour or in need of vasoactive drugs. [2] Acute kidney injury was defined as absolute rise in serum creatinine of ≄0.3 mg/dL (≄26.4 ÎŒmol/L), increase in serum creatinine of ≄50%, reduction in urine output, defined as <0.5 mL/kg per hour for more than 6 hours.…”
Section: Defi Nitionmentioning
confidence: 99%